Pendampingan Pengenalan Slang Word Menggunakan Aplikasi Media Sosial Tiktok pada Anak-Anak Kp.Golat Desa Pangkalan - Anang Jamaludin; Susanti Susanti; Dede Imtihanudin; Eneng Liah Khoiriyah; Eka Dewi Fitrohunisa (Kolaborasi: Jurnal Pengabdian Masyarakat, 2023)
Introduction: Slang is a branch of Indonesian as a language of social communication. The term began to appear in the late 1980s. Slang is often used as a means of communication among teenagers and even children in a group within a certain period of time. Indeed, children and teenagers have their own language of expression. Objective: This study aims to investigate the effect of the existence of slang on tiktok social media on increasing children's knowledge in understanding slang. Method: The research method used is a lecture method with a descriptive design on a group of children from Kp.Golat.  Result: The implementation of assistance in the introduction of Slang Word (Slang Language) is given to children in Kampung Golat, Pangkalan Village, Pandeglang Regency as mentoring participants and is carried out in the Kp.Golat environment so that they can add insight and can understand about slang languages contained in the Tiktok social media application in order to equip.children.in.facing.technological.developments.and.the.times. Conclusion: By providing assistance regarding the introduction of slang to golat village children, it has proven to be useful for increasing knowledge and understanding of slang found on tiktok social media